Postgraduate Education in Disaster Health and Medicine - Khalid Yousif Ahmed Algaali; Ahmadreza eDjalali; Francesco eDella Corte; Mohamed Ahmed Ismail; Pier Luigi eIngrassia (Frontiers Media S.A., 2015)
Introduction: Education is key to effective disaster management. This study reviews several postgraduate educational programs in disaster medicine.Methods: This cross-sectional study was conducted in two stages between October 2011 and February 2012. An online search was completed, followed by a web-based survey to collect information on key aspects of the identified programs.Results: Thirty-four programs were identified, worldwide. Public health was the main focus in 84% of these. E-learning was the preferred mode of instruction in 25% of cases. Most programs were accredited either nationally or internationally. Tuitions fees were the main source of funding.Conclusions: There is a dearth of postgraduate training programs in disaster health and medicine. This applies especially to Asia, which is also the most vulnerable area. Educational provision must be strengthened in Asia and in low-and middle-income countries to enhance capacity building in the health management of disasters.